Survival of trisomy 18 (Edwards syndrome) and trisomy 13 (Patau Syndrome) in England and Wales: 2004–2011. Issue 10 (15th August 2013) - Wu, Jianhua; Springett, Anna; Morris, Joan K.
Abstract The aim of this study is to determine the survival of live births with trisomy 18 and trisomy 13 and their variants. Information on live births with trisomy 18 or trisomy 13 recorded in the National Down Syndrome Cytogenetic Register (NDSCR) was linked by the NHS Information Centre to obtain information about survival. Survival was known for 326 (88%) of live births with trisomy 18 and 142 (82%) of live births with trisomy 13 born in England and Wales between 2004 and 2011. The median survival time for live births with full trisomy 18 was 14 days and with full trisomy 13 was 10 days, the 3‐month survival was 20% and 18%, respectively, and the 1‐year survival for both syndromes was 8%. The 1‐year survival for live births with trisomy 18 mosaicism (n = 17) was 70%, for those with trisomy 13 mosaicism (n = 5) was 80% and for those with partial trisomy 13 (Robertsonian translocations) (n = 17) was 29%. This study is based on the largest data set on survival for live births with trisomy 18 and trisomy 13. Although median survival for these children is 2 weeks or less, about one in five survive for 3 months or more and about 1 in 12 survive for 1 year or more. We suggest that these survival rates are used in counselling as well as the median survival time. © 2013 Wiley Periodicals, Inc.